Analysis of Multichannel EEG Patterns During Human Sleep: A Novel Approach - Krauß, Patrick; Schilling, Achim; Bauer, Judith; Tziridis, Konstantin; Metzner, Claus; Schulze, Holger; Traxdorf, Maximilian (Frontiers in Human Neuroscience, 2018)
Classic visual sleep stage scoring is based on electroencephalogram (EEG) frequency band analysis of 30 s epochs and is commonly performed by highly trained medical sleep specialists using additional information from submental EMG and eye movements electrooculogram (EOG). In this study, we provide the proof-of-principle in 40 subjects that sleep stages can be consistently differentiated solely on the basis of spatial 3-channel EEG patterns based on root-mean-square (RMS) amplitudes. The polysomnographic 3-channel EEG data are pre-processed by RMS averaging over intervals of 30 s leading to spatial cortical activity patterns represented by 3-dimensional vectors. These patterns are visualized using multidimensional scaling (MDS), allowing a comparison of the spatial cortical activity patterns with the conventional visual sleep scoring system according to the American Academy of Sleep Medicine (AASM). Spatial cortical activity patterns based on RMS amplitudes naturally divide into different clusters that correspond to visually scored sleep stages. Furthermore, these clusters are reproducible between different subjects. Especially the cluster associated with the REM sleep stage seems to be very different from the one associated with the wake state. This study provides a proof-of-principle that it is possible to separate sleep stages solely by analyzing spatially distributed EEG RMS amplitudes reflecting cortical activity and without classical EEG feature extractions like power spectrum analysis.
EVALuna2:35750

Bioelectric impedance phase angle is associated with hospital mortality of geriatric patients - Wirth, Rainer; Volkert, Dorothee; Roesler, A.; Sieber, Cornel; Bauer, Judith (Archives of gerontology and geriatrics, 2010)
Malnutrition is regularly associated with weight loss and changes in body composition, which lead to an increase in disability, complications and mortality. Bioelectric impedance analysis (BIA) is a simple and non-invasive bedside body composition analysis technique. In particular, bioelectric impedance phase angle (PA) has been shown to predict prognosis and mortality in several clinical conditions. The purpose of this study was to determine the relationship of BIA measurements and hospital mortality in multimorbid geriatric patients. The data obtained from the routine clinical admissions of 1071 consecutive patients (783 women and 288 men, age 81.4 +/- 8.5 years) to a geriatric hospital unit was analyzed retrospectively. A significant difference of PA (50 kHz) between survivors (4.2 +/- 1.1 degrees) and non-survivors (3.6 +/- 1.2 degrees; p < 0.001) of the hospital stay could be detected. Subjects with a PA below 3.5 degrees showed a significant fourfold increased hospital mortality of 20% (95% CI = 15-24%) compared to all other subjects (5%; 95% CI = 4-7%). No calculated parameters of BIA reflecting body composition were associated with hospital mortality. Although the extent to which the PA may be regarded as a marker of nutritional state is still controversial, it was associated with hospital mortality in geriatric patients. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Bioelectric impedance; Hospital mortality; Malnutrition of elderly; Phase angle; Geriatric patients

Consensus definition of sarcopenia, cachexia and pre-cachexia: Joint document elaborated by Special Interest Groups (SIG) "cachexia-anorexia in chronic wasting diseases" and "nutrition in geriatrics" - Muscaritoli, M.; Anker, S. D.; Argiles, J.; Aversa, Z.; Bauer, Judith; Biolo, Gianni; Boirie, Y.; Bosaeus, I.; Cederholm, T.; Costelli, P.; Fearon, K. C.; Laviano, A.; et al. (Clinical Nutrition, 2010)
Chronic diseases as well as aging are frequently associated with deterioration of nutritional status, loss muscle mass and function (i.e. sarcopenia), impaired quality of life and increased risk for morbidity and mortality. Although simple and effective tools for the accurate screening, diagnosis and treatment of malnutrition have been developed during the recent years, its prevalence still remains disappointingly high and its impact on morbidity, mortality and quality of life clinically significant. Based on these premises, the Special Interest Group (SIG) on cachexia-anorexia in chronic wasting diseases was created within ESPEN with the aim of developing and spreading the knowledge on the basic and clinical aspects of cachexia and anorexia as well as of increasing the awareness of cachexia among health professionals and care givers. The definition, the assessment and the staging of cachexia, were identified as a priority by the SIG. This consensus paper reports the definition of cachexia, pre-cachexia and sarcopenia as well as the criteria for the differentiation between cachexia and other conditions associated with sarcopenia, which have been developed in cooperation with the ESPEN SIG on nutrition in geriatrics. (C) 2009 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: Chronic diseases; Aging; Pre-cachexia; Cachexia; Anorexia; Sarcopenia

C-terminal Agrin Fragment as a potential marker for sarcopenia caused by degeneration of the neuromuscular junction - Drey, Michael; Sieber, Cornel; Bauer, Judith; Uter, Wolfgang; Dahinden, P.; Fariello, R. G.; Vrijbloed, J. W. (Experimental Gerontology, 2013)
Introduction: Sarcopenia is considered to be an enormous burden for both the individuals affected and for society at large. A multifactorial aetiology of this geriatric syndrome has been discussed. Amongst other pathomechanisms, the degeneration of the neuromuscular junction (NMJ) may be of major relevance. The intact balance between the pro-synaptic agent agrin and the anti-synaptic agent neurotrypsin ensures a structurally and functionally intact NMJ. Excessive cleavage of the native motoneuron-derived agrin by neurotrypsin into a C-terminal Agrin Fragment (CAF) leads to functional disintegration at the NMJ and may consecutively cause sarcopenia. The present study evaluates the hypothesis that CAF serum concentration is a potential marker for the loss of appendicular lean mass in older adults. It also explores how CAF concentration is influenced by vitamin D supplementation and physical exercise.Method: Serum was taken from 69 (47 female) prefrail community-dwelling older adults participating in a training intervention study to measure the CAF concentration using the Western blot technique. All participants were supplemented orally with vitamin D3 before the training intervention period commenced. Appendicular lean mass (aLM) was evaluated by dual energy X-ray absorptiometry. Multiple linear regression models were used to identify factors significantly associated with CAF concentration.Results: Appendicular lean mass, age and sex were identified as significant explanatory factors for CAF concentration. Gait speed and hand grip strength were not associated with CAF concentration. Male participants showed a strong correlation (r=-0.524) between CAF serum concentration and aLM, whereas this was not the case (r=-0.219) in females. Vitamin D supplementation and physical exercise were significantly associated with a reduction in CAF concentration, especially in participants with initially high CAF concentrations.Conclusions: C-terminal Agrin Fragment could be a potential marker for identifying sarcopenia in a subgroup of affected individuals in the future. The decline of muscle mass seems to be a CAF-associated process in males, whereas the situation in females may be more complex and multifactorial. CAF concentration is reduced by vitamin D supplementation and physical exercise and therefore suggests a potentially positive effect on NMJs. Further prospective studies of sarcopenic patients in addition to muscle biopsy and electromyographical investigations are planned to verify the external validity of the CAF concept. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Sarcopenia; Neuromuscular junction; Agrin; Neurotrypsin; Exercise; Vitamin D

Diagnostic Yield and Novel Candidate Genes by Exome Sequencing in 152 Consanguineous Families With Neurodevelopmental Disorders - Reuter, Miriam; Tawamie, Hasan; Buchert, Rebecca; Gebril, Ola Hosny; Froukh, Tawfiq; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Krumbiegel, Mandy; Zweier, Christiane; Hoyer, Juliane; Eberlein, Karolin; et al. (JAMA Psychiatry, 2017)
Autosomal recessive inherited neurodevelopmental disorders are highly heterogeneous, and many, possibly most, of the disease genes are still unknown.To promote the identification of disease genes through confirmation of previously described genes and presentation of novel candidates and provide an overview of the diagnostic yield of exome sequencing in consanguineous families.Autozygosity mapping in families and exome sequencing of index patients were performed in 152 consanguineous families (the parents descended from a same ancestor) with at least 1 offspring with intellectual disability (ID). The study was conducted from July 1, 2008, to June 30, 2015, and data analysis was conducted from July 1, 2015, to August 31, 2016.Of the 152 consanguineous families enrolled, 1 child (in 45 families [29.6%]) or multiple children (107 families [70.4%]) had ID; additional features were present in 140 of the families (92.1%). The mean (SD) age of the children was 10.3 (9.0) years, and 171 of 297 (57.6%) were male. In 109 families (71.7%), potentially protein-disrupting and clinically relevant variants were identified. Of these, a clear clinical genetic diagnosis was made in 56 families (36.8%) owing to 57 (likely) pathogenic variants in 50 genes already established in neurodevelopmental disorders (46 autosomal recessive, 2 X-linked, and 2 de novo) or in 7 previously proposed recessive candidates. In 5 of these families, potentially treatable disorders were diagnosed (mutations in PAH, CBS, MTHFR, CYP27A1, and HIBCH), and in 1 family, 2 disease-causing homozygous variants in different genes were identified. In another 48 families (31.6%), 52 convincing recessive variants in candidate genes that were not previously reported in regard to neurodevelopmental disorders were identified. Of these, 14 were homozygous and truncating in GRM7, STX1A, CCAR2, EEF1D, GALNT2, SLC44A1, LRRIQ3, AMZ2, CLMN, SEC23IP, INIP, NARG2, FAM234B, and TRAP1. The diagnostic yield was higher in individuals with severe ID (35 of 77 [45.5%]), in multiplex families (42 of 107 [39.3%]), in patients with additional features (30 of 70 [42.9%]), and in those with remotely related parents (15 of 34 [44.1%]).Because of the high diagnostic yield of 36.8% and the possibility of identifying treatable diseases or the coexistence of several disease-causing variants, using exome sequencing as a first-line diagnostic approach in consanguineous families with neurodevelopmental disorders is recommended. Furthermore, the literature is enriched with 52 convincing candidate genes that are awaiting confirmation in independent families.
EVALuna2:9388

Drug-Induced Sleep Endoscopy (DISE) with Target Controlled Infusion (TCI) and Bispectral Analysis in Obstructive Sleep Apnea - Traxdorf, Maximilian; Tschaikowsky, Klaus; Scherl, Claudia; Bauer, Judith; Iro, Heinrich; Angerer, Florian (Journal of Visualized Experiments, 2016)
The aim of this study was to establish a standardized protocol for drug-induced sleep endoscopy (DISE) to differentiate obstruction patterns in obstructive sleep apnea (OSA). Target-controlled infusion (TCI) of the sedative propofol was combined with real-time monitoring of the depth of sedation using bispectral analysis. In an observational study 57 patients (mean age 44.8 years, ± SD 10.5; mean apnea hypopnea Index (AHI) 30.8/hr, ± SD 21.6, mean BMI 28.2 kg/m(2), ± SD 5.3) underwent cardiorespiratory polysomnography followed by DISE with TCI and bispectral analysis. Sleep was induced solely by the intravenous infusion of propofol with a TCI-pump, with an initial target plasma level of 2.0 µg/ml. Under continuous monitoring of the patient's respiration, state of consciousness and value of the bispectral analysis, the target plasma propofol level was raised in steps of 0.2 µg/ml/2 min until the desired depth of sedation was reached. The mean value of the bispectral analysis at the target depth of sedation was determined and the obstruction patterns during DISE-TCI-bispectral analysis then classified according to the VOTE-system. Subsequently the results were analyzed according to polysomnographic and anthropometric data. The occurrence of multilevel obstruction sites across all degrees of severity of OSA clarifies the need for sleep endoscopy prior to upper airway surgery. The advantage of this technique is the reproducibility of the protocol even for heterogeneous groups of patients. In addition, the gradual controlled and standardized increase of the plasma level of propofol with real-time control of the bispectral index leads to a precisely controllable depth of sedation. The DISE-TCI-bispectral analysis procedure is a step towards a required reproducible protocol of sleep endoscopy - capable of standardization. However it is not yet known whether these observed obstruction patterns also correspond to findings in natural sleep.
EVALuna2:16743

Frequency of Malnutrition in Older Adults: A Multinational Perspective Using the Mini Nutritional Assessment - Kaiser, Matthias; Bauer, Judith; Raemsch, Christiane; Uter, Wolfgang; Guigoz, Yves; Cederholm, Tommy; Thomas, David R.; Anthony, Patricia S.; Charlton, Karen E.; Maggio, Marcello; Tsai, Alan C.; Vellas, Bruno; et al. (Journal of the American Geriatrics Society, 2010)
OBJECTIVESTo provide pooled data on the prevalence of malnutrition in elderly people as evaluated using the Mini Nutritional Assessment (MNA).DESIGNRetrospective pooled analysis of previously published datasets.SETTINGHospital, rehabilitation, nursing home, community.PARTICIPANTSFour thousand five hundred seven people (75.2% female) with a mean age of 82.3.MEASUREMENTSThe prevalence of malnutrition in the combined database and in the four settings was examined.RESULTSTwenty-four data sets with information on full MNA classification from researchers from 12 countries were submitted. In the combined database, the prevalence of malnutrition was 22.8%, with considerable differences between the settings (rehabilitation, 50.5%; hospital, 38.7%; nursing home, 13.8%; community, 5.8%). In the combined database, the "at risk" group had a prevalence of 46.2%. Consequently, approximately two-thirds of study participants were at nutritional risk or malnourished.CONCLUSIONThe MNA has gained worldwide acceptance and shows a high prevalence of malnutrition in different settings, except for the community. Because of its specific geriatric focus, the MNA should be recommended as the basis for nutritional evaluation in older people.
Keywords: malnutrition; undernutrition; Mini Nutritional Assessment; elderly; nutritional screening

Malnutrition, sarcopenia and cachexia in the elderly: from pathophysiology to treatment - conclusions of an international meeting of experts, sponsored by the BANSS Foundation - Bauer, Judith; Wirth, Rainer; Volkert, D.; Werner, H.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2008)
Keywords: malnutrition; sarcopenia; cachexia; elderly; pathophysiology

Peak-bone-mass development in young adults: effects of study program related levels of occupational and leisure time physical activity and exercise. A prospective 5-year study - Kemmler, Wolfgang; Bebenek, Michael; von Stengel, Simon; Bauer, Judith (Osteoporosis international, 2015)
Young adulthood is characterized by profound life-style changes. This study suggests that reduction of sport or exercise, induced by alteration of the occupational situation, negatively impacts generation/maintenance of peak bone mass. In order to compensate occupational-related reductions of physical activity, workplace exercise programs will be helpful.Only few studies have determined the effect of physical activity or physical exercise on bone mineral density (BMD) in the period of late skeletal maturation, i.e. around peak bone mass. The aim of this article was to determine the long-term effect of different levels of physical activity and exercise directly and indirectly derived by occupation during young adulthood.Sixty-one male and female dental students (DES) and 53 male and female sport students (SPS) 21 ± 2 years old were accompanied over the course (4.8 ± 0.5 years) of their study program. BMD at the lumbar spine (LS), hip, and whole body (WB) were determined using dual-energy X-ray absorptiometry.Parameters of physical activity increased non-significantly in both groups with no relevant differences between the groups. Indices of exercise, however, increased significantly in the SPS group while a significant decrease was assessed for the DES group. Independent of gender, BMD of the SPS increased significantly (p <= 0.007) at all skeletal sites (LS, 2.4 ± 3.9 %; hip, 1.6 ± 3.5 %; WB, 1.8 ± 2.8 %) while BMD of the DES remained unchanged at LS (-0.6 ± 4.4 %, p = 0.432) and WB (0.5 ± 1.9 %, p = 0.092) but decreased significantly at the hip (-1.9 ± 4.3 %, p = 0.010). BMD-changes at LS, hip, and WB differ significantly between SPS and DES (p <= 0.017). Results remained unchanged after adjusting for baseline BMD-values that differed (p = 0.030 to p = 0.082) in favor of the SPS group.Changes of exercise levels directly or indirectly caused by occupational factors during young adulthood significantly affected generation and/or maintenance of peak bone mass. Compensatory exercise is thus highly relevant for bone health of young adults.
EVALuna2:10101

S100B in serum and saliva: a valid invasive or non-invasive biomarker in obstructive sleep apnea? - Traxdorf, Maximilian; Wendler, O.; Tziridis, Konstantin; Bauer, Judith; Scherl, C. (European Review for Medical and Pharmacological Sciences, 2016)
OBJECTIVE: The aim of this prospective study was to determine whether serum or saliva S100B could be established as an invasive or non-invasive biomarker of cerebrovascular stress due to chronic intermittent hypoxia in obstructive sleep apnea (OSA). PATIENTS AND METHODS: S100B levels in serum and saliva were measured by an enzyme-linked immunosorbent assay (ELISA) in 40 patients with polysomnographically confirmed OSA (n=34) or ronchopathy (n=6) and 20 control subjects (n=20). We also investigated four healthy volunteers (n=4) to determine whether the S100B levels in serum and saliva are dependent on the time of day. RESULTS: Serum S100B was significantly higher in OSA than in healthy control subjects (p=0.007), although it was not related to the severity of OSA and was independent of age, sex, and subjective daytime symptoms. Values of S100B in saliva showed a marked scatter, so there was no significant difference between the OSA group and controls (p=0.62). We did not find that S100B levels in either serum or saliva depended on the time of day (p=0.53; p=0.91). CONCLUSIONS: Serum S100B allows us to discriminate healthy subjects from patients with OSA. However, it does not live up to its promise as a valid invasive predictor of OSA, since it does not correlate with the severity of the disease. Also, S100B in saliva is not suitable for use as a non-invasive biomarker to detect hypoxia-induced cerebrovascular stress in OSA. This finding prevents an S100B saliva-based assessment of risk or possible extent of structural brain damage, ruling out the possibility of non-invasive home monitoring of compliance and therapeutic efficacy in cases of OSA on treatment.
EVALuna2:33219

Sarcopenia and frailty: A clinician's controversial point of view - Bauer, Judith; Sieber, Cornel (Experimental Gerontology, 2008)
Sarcopenia and frailty are both highly relevant entities with regard to functionality and independence in the elderly. The term sarcopenia has been introduced already in the late 80s and since then attracted the interest of many researchers, the majority being interested in its pathophysiology. Nevertheless there is still no consensus on the definition of sarcopenia and its diagnosis. Despite its relevance for functionality and autonomy most clinicians caring for the elderly are not familiar with sarcopenia and it has not become part of the routine geriatric evaluation.The concept of frailty has recently been supported by the introduction of two new working definitions. Since then clinical research on frailty has steeply increased. The influence of frailty on different age-associated diseases has been investigated and populations at risk for complications of medical or operative therapy are identified with the help of this concept. Simultaneously the pathophysiologic mechanisms involved in the development of frailty are explored.While sarcopenia may be regarded as a clinical sign that is not specific for the elderly, frailty may be seen as a multidimensional geriatric syndrome which implies a greater relevance for the clinician than the one dimensional approach of sarcopenia. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: sarcopenia; frailty; definition; diagnosis; pathophysiology

Sarcopenia in Nursing Home Residents - Bauer, Judith; Kaiser, Matthias; Sieber, Cornel (Journal of the American Medical Directors Association, 2008)
The age-associated loss of muscle mass and muscle strength described by the term sarcopenia is highly relevant for functionality among nursing home residents. Nevertheless, the scientific literature concentrating on sarcopenia in this population is scarce. For practical reasons, common definitions of this entity, which rely on dual energy x-ray absorptiometry (DEXA) and bioimpedance analysis (BIA), cannot be applied in this setting. Anthropometric measurements like arm muscle circumference and calf circumference seem to be most suitable. Handgrip may be used as an alternative. Prevalence data show a wide range but are mostly high. There is a close association of the degree of sarcopenia with dependence among residents. The pathophysiology of sarcopenia in this population is strongly influenced by comorbidity and often there is significant overlap with the cachexia syndrome.At present, physical exercise is regarded to be the most promising therapeutic option, with resistance training being superior to endurance programs. Physical exercise has been successful even among Alzheimer patients and physically restrained residents. It has to be accompanied by the provision of adequate and diverse meals based on individual energy and nutrient requirements. Special attention should be paid to the treatment of vitamin D deficiency if present. New therapeutic options include Whole Body Vibration, oral supplements with essential amino acids and leucine, ACE-inhibitors, and cytokine-modifying drugs.
Keywords: Sarcopenia; nursing home; pathophysiology; diagnosis; treatment

The influence of obstructive sleep apnea and continuous positive airway pressure on the nasal microbiome - Lenk, Christian; Meßbacher, Maria-Elena; Abel, Judith; Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Sievert, Matti; Wirtz, Stefan; Marxreiter, Franz; Winkler, Jürgen; Iro, Heinrich; Traxdorf, Maximilian (European Review for Medical and Pharmacological Sciences, 2023)
OBJECTIVE: The aim of this study was to investigate the influence of obstructive sleep apnea and continuous positive airway pressure on the nasal microbiome. PATIENTS AND METHODS: Endonasal swabs from the olfactory groove of 22 patients with moderate and severe obstructive sleep apnea (OSA) and a control group of 17 healthy controls were obtained at the Department of Otorhinolaryngology of the Friedrich-Alexander-Universität Erlangen-Nürnberg. 16S rRNA gene sequencing was performed to further evaluate the endonasal microbiome. In a second step, the longitudinal influence of continuous positive airway pressure (CPAP) therapy on the nasal microbiome was investigated (3-6 and 6-9 months). RESULTS: Analysis of the bacterial load and β-diversity showed no significant differences between the groups, although patients with severe OSA showed increased α-diversity compared to the control group, while those with moderate OSA showed decreased α-diversity. The evaluation of longitudinal changes in the nasal microbiota during CPAP treatment showed no significant difference in α- or β-diversity. However, the number of bacteria for which a significant difference between moderate and severe OSA was found in the linear discriminant analysis decreased during CPAP treatment. CONCLUSIONS: Long-term CPAP treatment showed an alignment of the composition of the nasal microbiome in patients with moderate and severe OSA as well as an alignment of biodiversity with that of the healthy control group. This change in the composition of the microbiome could be both part of the therapeutic effect in CPAP therapy and a promoting factor of the adverse side effects of the therapy. Further studies are needed to investigate whether the endonasal microbiome is related to CPAP compliance and whether CPAP compliance can be positively influenced in the future by therapeutic modification of the microbiome.
CRIS-Team WoS Importer:2023-05-26

The Mini Nutritional Assessment (R)-Its History, Today's Practice, and Future Perspectives - Bauer, Judith; Kaiser, Matthias J.; Anthony, Patricia; Guigoz, Yves; Sieber, Cornel (Nutrition in Clinical Practice, 2008)
In the early 1990s, the Mini Nutritional Assessment(R) (MNA; Nestle Nutrition, Vevey, Switzerland) was developed for nutrition screening in the elderly. Since then, it became the most established and widespread screening tool for older persons and has been translated into many different languages. The MNA shows prognostic relevance with regard to functionality, morbidity, and mortality of the elderly in different settings. This article recalls the development of the MNA with its short form (MNA-SF) and reviews the literature, focusing on the most recent publications. Specific features of the application of the MNA in different settings (community, nursing home, hospital) are considered. Minor shortcomings of the tool, such as the resources and the cooperation necessary for completion of the MNA, are discussed. Future options for the adaptation of this valuable tool are briefly characterized. (Nutr Clin Pract. 2008;23:388-396)
Keywords: nutrition assessment; nutrition status; aged; geriatrics; geriatric assessment; malnutrition; protein-energy malnutrition

The Motor Unit Number Index (MUNIX) in sarcopenic patients - Drey, Michael; Groesch, C.; Neuwirth, C.; Bauer, Judith; Sieber, Cornel (Experimental Gerontology, 2013)
Introduction: The cause of sarcopenia is still not fully understood. A multifactorial aetiology is discussed. Neurodegenerative aspects in the genesis of sarcopenia, such as loss of motoneurons, have not yet been explored to a sufficient extent.Method: The Motor Unit Number Index (MUNIX) is a method for assessing the number and size (Motor Unit Size Index - MUSIX) of Motor Units (MUs) using the Compound Muscle Action Potential (CMAP) and the Surface electromyographic Interference Pattern (SIP). This method was used to study the hypothenar muscle in the right hand of 27 sarcopenic patients.Results: The mean MUNIX (111 +/- 51) of all investigated sarcopenic patients lies between the mean MUNIX of healthy persons and the mean MUNIX of ALS patients. 25% of sarcopenic patients exhibit pathologic values for both MUNIX (<80) and MUSIX (> 100 mu V). A strong correlation (r= 0.75, p<0.001) between MUSIX and the reciprocal value of MUNIX was identified.Conclusion: It was demonstrated for the first time by applying the MUNIX technique that loss of motoneurons plays a pathogenic role in the onset of sarcopenia. This was shown in 25% of sarcopenic participants who exhibited pathologic values for both MUNIX and MUSIX. Nerve sprouting seems to be an important mechanism of compensation for loss of motoneurons, reflected by the strong correlation between MUNIX and MUSIX. Use of MUNIX leads to the identification of a distinct subgroup of sarcopenic patients, which might have a major impact on future diagnostic and therapeutic concepts. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Sarcopenia; Motoneuron; Neuromuscular; MUNIX; Elderly

Validation of the Mini Nutritional Assessment short-form (MNAA (R)-SF): A practical tool for identification of nutritional status - Kaiser, Matthias; Bauer, Judith; Ramsch, C.; Uter, Wolfgang; Guigoz, Y.; Cederholm, T.; Thomas, D. R.; Anthony, P.; Charlton, K. E.; Maggio, M.; Tsai, A. C.; Grathwohl, D.; et al. (Journal of Nutrition, Health & Aging, 2009)
To validate a revision of the Mini Nutritional Assessment short-form (MNAA (R)-SF) against the full MNA, a standard tool for nutritional evaluation.A literature search identified studies that used the MNA for nutritional screening in geriatric patients. The contacted authors submitted original datasets that were merged into a single database. Various combinations of the questions on the current MNA-SF were tested using this database through combination analysis and ROC based derivation of classification thresholds.Twenty-seven datasets (n=6257 participants) were initially processed from which twelve were used in the current analysis on a sample of 2032 study participants (mean age 82.3y) with complete information on all MNA items. The original MNA-SF was a combination of six questions from the full MNA. A revised MNA-SF included calf circumference (CC) substituted for BMI performed equally well. A revised three-category scoring classification for this revised MNA-SF, using BMI and/or CC, had good sensitivity compared to the full MNA.The newly revised MNA-SF is a valid nutritional screening tool applicable to geriatric health care professionals with the option of using CC when BMI cannot be calculated. This revised MNA-SF increases the applicability of this rapid screening tool in clinical practice through the inclusion of a "malnourished" category.
Keywords: Mini Nutritional Assessment; short-form; weight; body mass index; calf circumference; elderly

Vitamin D Blood levels in Nursing home - Status Quo and Related to physical Functionality - Diekmann, Rebecca; Winning, Katrin; Bauer, Judith; Lesser, Stephanie; Stehle, P.; Sieber, Cornel; Volkert, Dorothee (Internist, 2013)